The Effect of Using Quizizz as a Quizzing Platform on Motivation and Learning Outcomes of Students in Informatics Subjects - Yoharmen Arnov; Sukardi; Giatman; Dedy Irfan (Postgraduate, University of Mataram, 2025)
This study aimed to analyze the effect of using Quizizz Paper Mode on students’ learning outcomes and motivation in Informatics subjects at SMK Negeri 2 Kepulauan Mentawai. A quasi-experimental design was employed with two grade X classes (16 students each) assigned to experimental and control groups. Data were collected through learning achievement tests, motivation questionnaires, observations, interviews, and documentation, and analyzed using quantitative and qualitative approaches. The results indicated that Quizizz Paper Mode significantly improved both learning outcomes and motivation compared to conventional methods. These findings highlight that gamification through Quizizz Paper Mode provides an adaptive solution for schools in areas with limited ICT infrastructure, such as Mentawai, by creating an engaging and interactive learning environment without relying on internet access or digital devices. The study implies that similar innovations could be implemented more broadly in under-resourced schools to support equitable learning opportunities in the digital era.